2011
DOI: 10.1007/s12223-011-0003-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing and antimicrobial resistance of Salmonella Enteritidis isolated from poultry, food, and humans in Serbia

Abstract: Molecular typing and resistotyping coupled with gyrA single nucleotide polymorphism (SNP) of 60 Salmonella Enteritidis (SE) isolates originated from poultry, food, and humans in Serbia is described. Molecular fingerprinting was performed by randomly amplified polymorphic DNA (RAPD) using four primers, and the diversity index (D) was 0.688. In combination with resistotyping and gyrA SNP, D increased to 0.828. A total of 23 genetic groups were obtained. When four RAPD primers were combined, epidemic isolates fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…In a previous investigation of a limited number of isolates, resistance to fluoroquinolones was not found, but 16.7% of Salmonella enterica serotype Enteritidis from humans were resistant to NAL [5]. The aim of the present study was to investigate the occurrence of quinolone resistance in a larger collection of S. Enteritidis isolates from human samples and to elucidate the mechanisms behind it.…”
Section: Introductionmentioning
confidence: 83%
“…In a previous investigation of a limited number of isolates, resistance to fluoroquinolones was not found, but 16.7% of Salmonella enterica serotype Enteritidis from humans were resistant to NAL [5]. The aim of the present study was to investigate the occurrence of quinolone resistance in a larger collection of S. Enteritidis isolates from human samples and to elucidate the mechanisms behind it.…”
Section: Introductionmentioning
confidence: 83%
“…Salmonella Enteritidis from one day old chicken was resistant to ampicillin (AMP), cephalothin (CFT), nalidixic acid (NAL) and tetracycline (TET). One isolate from stool was resistant to AMP, TET, trimetoprimsulfamethoxasole (SXT) and another isolate from stool exhibited resistance to AMP, TET, SXT and neomycin (NEO) (Kozoderović et al, 2011). There was an increase of Salmonella Enteritidis isolates in Serbia in 2005 and clonal spread was suspected.…”
Section: Point Mutations In Topoisomerase Genes Of Salmonellamentioning
confidence: 99%
“…According to research conducted in our country multiresistant Salmonella strains are present in poultry, and the findings of some authors point to the need for the introduction of the laboratory practice of adequate system of molecular standardization of strains and monitoring of resistance, particularly resistance to quinolones in Salmonella. 19,20 Monitoring of resistance in S. Infantis is very important due to the frequent occurrence of this serotype that is mainly derived from poultry. According to research Velhner et al 21 PFGE analysis showed that in Serbia S. Infantis isolates have similar genetic profile indicating a clonal spread of resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Control measures include disinfection of buildings and equipment, rodent control, vaccination, treatment, and laboratory testing. Based on the research of some authors, 19,20 there is a need for the application of molecular methods in antibiotic resistant strains in order to reveal the mechanisms of resistance occurrence and origin of strains (epizootiological and possibly epidemiological) or the origin of their resistant phenotypic traits.…”
Section: Resultsmentioning
confidence: 99%